Organizational Scholarship and the Eradication of Global Poverty - Pearce, Jone L. (Academy of Management Journal, 2005)
The article discusses the relevance of organizational management to efforts at eradicating global poverty. Affluent nations are often characterized by the existence of large, meritocratic bodies free of government control, and governance quality in the form of states able to exert control over sovereign territory and public officials. Moreover, large organizations both create and disperse wealth among a population. Organizational scholars can bring their expertise to bear on these wealth-creating organizations and help governments devise policies that promote them.